Catastrophic health expenditure, incidence, trend and socioeconomic risk factors in China: A systematic review and meta-analysis - Zhang, Fangkai; Jiang, Jianjun; Yang, Min; Zou, Kun; Chen, Dandi (Frontiers in Public Health, 2023)
Abstract Objective To evaluate the incidence and trend of catastrophic health expenditures (CHE) in China over the past 20 years and explore the socio-economic factors affecting China’s CHE rate. Methods The systematic review was conducted according to the Cochrane Handbook and reported according to PRISMA. We searched English and Chinese literature databases including PubMed, EMbase, web of science, CNKI, Wan Fang, VIP, and CBM (Sino Med) for empirical studies on the CHE rate in China and its associated social-economic factors from January 2000 to June 2020. Study selection, data extraction, and quality appraisal were conducted by two reviewers. The secular trend of the CHE rate was examined, and factors that may be associated with CHE were explored using subgroup analysis and meta-regression. Results 118 eligible studies with 1771726 participants were included. From 2000 to 2020, the overall CHE rate was (25.2%, 95% CI: 23.4%-26.9%) in China. The CHE rate continued to rise from 13.0% in 2000 to 32.2% in 2020 in the general population. The CHE rate was higher in urban areas than in rural areas , higher in the western than the northeast, eastern, and central region, in the elderly than non-elderly, in low-income groups than non-low-income groups, in people with cancer, chronic infectious disease, cardio-cerebro-vascular diseases (CCVD) than non-chronic disease group, in people with NCMS than URBMI and UEBMI. Multiple meta-regression analysis found that low-income, cancer, CCVD, unspecified medical insurance type, definition 1 and definition 2 was correlated with CHE rate, while other factors were all non-significant correlation. Conclusion In the past two decades, the CHE rate in China has been rising. The continuous rise of health expenditures may be an important reason for the increasing CHE rate. Aging, income level, and health status affect the CHE rate. Therefore, it is necessary to find ways to meet the medical needs of residents and at the same time to control the unreasonable rapid increase of health expenditures in China.